أثر التردد بين الضبط والتقريب في تقويض دائرة الخلاف المصطلحي - Adjdir Nasreddine (Universitas Negeri Jakarta, 2019)
The problem in which the nation falls in this crisis is the problem of terminology, and often fallacies occur in buildings not in meanings.Therefore, he must escape from the nation who renounces the manifestations of discord and disagreement to the right and equity. The study comes to establish the theory of undermining the dispute by arbitrating the meanings of the desired terminology.